Organisational factors that facilitate research use in public health policy-making: a scoping review - Mette Winge Jakobsen; Leena Eklund Karlsson; Thomas Skovgaard; Arja R. Aro (BMC, 2019)
Abstract Background Although important syntheses and theoretical works exist in relation to understanding the organisational factors that facilitate research use, these contributions differ in their scope and object of study as well as their theoretical underpinnings. Therefore, from an exploratory angle, it may be useful to map out the current literature on organisational factors of research use in public health policy-making when revisiting existing theories and frameworks to gain further theoretical insights. Methods Herein, a scoping review technique and thematic content analysis were used to bring together findings from both synthesised and empirical studies of different types to map out the organisational factors that facilitate research use in public health policy-making. Results A total of 14 reviews and 40 empirical studies were included in the analysis. These were thematically coded and the intra-organisational factors reported as enabling research use were examined. Five main categories of organisational factors that advance research use in policy organisations - (1) individual factors, (2) the management of research integration, (3) organisational systems and infrastructures of research use, (4) institutional structures and rules for policy-making, and (5) organisational characteristics - were derived as well as 18 subcategories and a total of 64 specific factors, where 27 factors were well supported by research. Conclusions Using a scoping review methodology, the intra-organisational factors influencing research use in policy-making (including individual factors) were systematically mapped and the theories applied in this area of research were assessed. The review findings confirm the importance of an intra-organisational perspective when exploring research use, showing that many organisational factors are critical facilitators of research use but also that many factors and mechanisms are understudied. The synthesis shows a lack of studies on politicians and the need for more theoretically founded research. Despite increased efforts to update the existing evidential and theoretical basis of research use, we still need frameworks that combine different approaches and theories to help us grasp the complex organisational mechanisms that facilitate research use in policy settings.